Inheritance and innovation in a colonial language: Towards a usage-based account of French Guianese Creole by William Jennings and Stefan Pfänder (2018). (2nd March 2019) - Siegel, Jason
Abstract : Inheritance and innovation in a colonial language: Towards a usage-based account of French Guianese Creole William Jennings and Stefan Pfänder (2018) London: Palgrave Macmillan. Pp. 240 ISBN: 978-3-319-61951-4